Testing critical reading - Erece, Francisca Lachica 1932- (s.n.], 1964)
The writer of the study points out the need for a critical reading test which can serve as basis or provide redirection for the teaching of reading in Philippine High Schools. The study demonstrates that the classroom teachers themselves can devise critical reading tests that may help in emphasizing the idea that the ultimate goal in teaching reading in high school is not merely to improve reading skills but to use reading as a means to stimulate thinking in response to printed matter and to regard the printed page with healthy skepticism so that the high school reader will not just accept anything printed simply because it is printed but to assess the statement or message of the printed words and to evaluate its authenticity, truth or value.